The Implementation of Artificial Intelligence (AI) in Enhancing Teachers’ English Speaking Skills: A Systematic Literature Review - Jumiarti Ketang Rejo; Muchlas Suseno (proceedings.icesy, 2026)
In the era of digital transformation, the integration of Artificial Intelligence (AI) has emerged as a promising solution to enhance English speaking proficiency. While many studies have focused on student learning outcomes, the implementation of AI specifically to improve teachers’ oral competence remains underexplored, despite teachers being the primary agents of educational change. This study aims to systematically review the implementation of AI in enhancing teachers’ English speaking skills, identifying effective platforms, key benefits, and challenges encountered during integration. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. A total of 25 relevant studies published between 2015 and 2026 were analyzed, with a focus on the use of AI in English Language Teaching (ELT). Findings indicate that AI tools, such as generative chatbots (ChatGPT) and speech recognition applications (Speechace, Elsa Speak), significantly improve teachers’ fluency, pronunciation accuracy, and confidence. However, implementation is often hindered by technical failures, limited pedagogical understanding of AI’s potential, and institutional gaps. Moreover, adoption by teachers is strongly influenced by individual cognition and professional agency. AI implementation offers a transformative approach to teacher professional development. To maximize its impact, structured technical training and policy support are necessary to bridge the gap between technological potential and classroom practice.